Explaining Mansplaing through Frameworks of Silencing, Epistemic Injustice, and Gender Metaphysics - Jankowska, Maria (Stance: an international undergraduate philosophy journal, 2025)
This paper argues that mansplaining is not just a conversational quirk but a mechanism of gender construction that reinforces systemic oppression. Drawing on the frameworks of silencing, epistemic injustice, and gender metaphysics, I come to the main thesis that mansplaining is one way gender is constructed, reinforcing hierarchical power structures and perpetuating societal inequality. As I further demonstrate, mansplaining functions as a form of epistemic violence that silences women and subordinates them within testimonial exchanges.